2012 6th Advanced Satellite Multimedia Systems Conference (ASMS) and 12th Signal Processing for Space Communications Workshop ( 2012
DOI: 10.1109/asms-spsc.2012.6333076
|View full text |Cite
|
Sign up to set email alerts
|

E-SSA satellite messaging return channel: Performance analysis and field trials results

Abstract: An open ITS platform combining interactive satellite services with other communication channels is being developed and evaluated in field trials within the SafeTRIP project [1]. Prototyping and in-field validation of a novel waveform for messaging return channel over satellite for land mobile is an important objective of the project. The overall system architecture has recently been standardized by ETSI under the name of S-MIM (S-band Mobile Interactive Multimedia). The messaging protocol, described in the Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…It can be observed that the T SDD performance in the laboratory tests increases with the background interference (caused by the background traffic load), as the IC process needs to remove higher interference power to decode the packets. In fact, the ESSA demodulator implementation in SafeTRIP is based on software defined radio [14] with a number of IC nodes connected in cascade.…”
Section: Dimensioning Examplesmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be observed that the T SDD performance in the laboratory tests increases with the background interference (caused by the background traffic load), as the IC process needs to remove higher interference power to decode the packets. In fact, the ESSA demodulator implementation in SafeTRIP is based on software defined radio [14] with a number of IC nodes connected in cascade.…”
Section: Dimensioning Examplesmentioning
confidence: 99%
“…It can be proven that the cases in which fragmentation and / or retransmissions are required can be expressed using Equation (14) by properly replacing the r.v. X as specified in Table I. (2) Case B: T bot < T ACK In this case, Equation (2) can be expressed as in Equation (15).…”
Section: A Queuing Theory-based Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the framework of the SafeTRIP project , an intelligent transport system open platform integrating the S‐MIM protocol has been developed and tested under real environment conditions. This in field evaluation of the platform represents the first on air test of the S‐MIM technology, although the E‐SSA wave form has already been validated on the field . With respect to these preliminary field trials of the E‐SSA wave form, the S‐MIM link layer (based on the Return Link Encapsulation (RLE) protocol ) has been developed and integrated in the open platform, providing thus statistics at link layer and Internet Protocol (IP) levels.…”
Section: Introductionmentioning
confidence: 99%